Safety and efficacy of paclitaxel drug-coated balloon in femoropopliteal in-stent restenosis. (2nd June 2020) - Anantha-Narayanan, Mahesh; Love, Keith; Nagpal, Sameer; Sheikh, Azfar Bilal; Regan, Christopher J.; Mena-Hurtado, Carlos
ABSTRACT: Introduction: The femoropopliteal (FP) segment is a common site of involvement in peripheral arterial disease (PAD) and endovascular therapy has been shown to be safe and effective in the treatment of FP disease. Self-expanding nitinol stents are now frequently used for the treatment of FP disease but in-stent restenosis (ISR) remains a major issue that can lead to recurrence of symptoms requiring repeated revascularizations. Compared to plain old balloon angioplasty (POBA), drug-coated balloons (DCBs) have shown promising results with reduction of ISR rates and target lesion revascularization (TLR). Areas covered: The aim of this review is to describe the mechanisms and classification of ISR and to summarize the available data on outcomes of all DCBs, especially in the treatment of FP ISR. Expert opinion: Currently available data supports the use of DCBs as a first-line therapy in patients with FP ISR, with lower rates of TLR and higher patency rates at 1-year follow-up, when compared to POBA. Further randomized studies are essential to evaluate longer term safety and efficacy of DCBs.